STUDY REGARDING THE EVOLUTION OF MOUNTAIN TOURISM AND RURAL MOUNTAIN TOURISM IN THE ROMANIAN CARPATHIANS DURING COVID-19 PANDEMIC - Andreea-Cristiana LINCA; Elena TOMA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study aimed to analyze the evolution of mountain tourism and rural mountain tourism in Romanian Carpathians during Covid19-Pandemic, to understand the level of damage that was done by this crisis in Romania in the tourism sector. For this we analyzed the comparison of the dynamic of tourists number between 2014-2019 and 2019-2020, and also the dynamic of the accommodation structures. All these researches were done by analyzing and generating reports provided by National Institute of Statistics (NIS). We discovered that even in pandemic times, investors still invested in accommodation structures, and that now more and more tourists choose rural mountain tourism because due to Covid-19 Pandemic they prefer to rent private villas, mountain huts, apartments or holiday homes, trying to maintain the social distance from others, and where they have the possibility to use their own facilities.